La La formación de profesores de matemáticas en Honduras - Turcios Carrazco, Uzzy Merary (2024)
Teacher training is a determining factor in the quality of an educational system, and it develops throughout the professional life. In mathematics there is a lot of interest in proposing improvements to curricula, teacher training processes and the preparation and implementation of educational materials. It would be interesting to know the way in which a mathematics teacher is trained in each country of the Central American region, to compare study plans, possibilities, opportunities, strengths and weaknesses. If these experiences are shared in teacher training, it is possible to create approaches that allow dialogues, discussions, ideas, comparisons and reflections on the way in which a mathematics teacher is trained and the type of experiences to which they are exposed. The countries of Central America, to face the challenges in education, must retake the unionist and integrating ideals of Francisco Morazán, whose saber was education. This article describes the training of mathematics teachers in Honduras, emphasizing the experiences that a student has to be a mathematics teacher.